(untitled) (Research, Society and Development, 2022)
The main focus of the research is to analyze, through the literature, the prevention of accidents by sharps among nursing professionals. The study is an integrative review research, this type of research follows six steps during its construction. The search was carried out in the electronic databases LILACS, BDENF, MEDLINE and SciELO. Data collection took place using the following descriptors: Containment of Biological Risks, Nurses, Occupational Risks and Intensive Care Units. The results showed that the procedures with the highest accident rates were: needle recapping (30%), medication administration (21.1%), incorrect handling of sharps and vascular puncture (13.15%). They showed that accidents with sharps occur due to inexperience as one of the factors that contribute to their occurrence, in addition to lack of concentration, haste, excess of tasks, emergencies, non-use of personal protective equipment, reduction of the team and stress. In addition, they observed that long service hours, night shifts, and weekend work significantly increased the risk of needlestick injuries. Nurses who work several days in a row and have shorter shifts are more likely to have sharps injuries. Due to the clinical complexity of patients and the variety of invasive procedures performed by the entire care team, the ICU is a critical environment that requires attention. Although there are few publications on this topic, it is clear that the main determinants of adherence are biosafety measures, such as the knowledge of nursing professionals, and preventive and promotional actions, such as the use of PPE.